Oropharyngeal dysphagia and cerebral palsy - Benfer, K.; Weir, K.; Bell, K.; Ware, R.; Davies, P.; Boyd, Roslyn (American Academy of Pediatrics, 2017)
OBJECTIVES: To determine the progression of oropharyngeal dysphagia (OPD) in preschoolaged children with cerebral palsy (CP) according to gross motor function. It was hypothesized that fewer children would have OPD at 60 months compared with 18 to 24 months (predominately Gross Motor Function Classification System [GMFCS] I-II). METHODS: Longitudinal population-based cohort of 179 children (confirmed CP diagnosis, born in Queensland in 2006-2009, aged 18-60 months at study entry [mean = 34.1 months} 11.9; 111 boys; GMFCS I = 46.6%, II = 12.9%, III = 15.7%, IV = 10.1%, and V = 14.6%] ). Children had a maximum of 3 assessments (median = 3, total n = 423 assessments). OPD was classified by using the Dysphagia Disorders Survey part 2 and rated from video by a certified pediatric speech pathologist. GMFCS was used to classify children's gross motor function. RESULTS: OPD prevalence reduced from 79.7% at 18 to 24 months to 43.5% at 60 months. There were decreasing odds of OPD with increasing age (odds ratio [OR] = 0.92 [95% confidence interval (CI) 0.90 to 0.95] ; P < .001) and increasing odds with poorer gross motor function (OR = 6.2 [95% CI 3.6 to 10.6]; P < .001). This reduction was significant for children with ambulatory CP (GMFCS I-II, OR = 0.93 [95% CI 0.90 to 0.96]; P < .001) but not significant for children from GMFCS III to V (OR [III] = 1.0 [95% CI 0.9 to 1.1] ; P = .897; OR [IV-V] = 1.0 [95% CI 1.0 to 1.1] ; P = .366). CONCLUSIONS: Half of the OPD present in children with CP between 18 and 24 months resolved by 60 months, with improvement most common in GMFCS I to II. To more accurately detect and target intervention at children with persisting OPD at 60 months, we suggest using a more conservative cut point of 6 out of 22 on the Dysphagia Disorders Survey for assessments between 18 and 48 months.